The Role of Motor Activity in the Social Integration of Disabled Individuals - Imas, Yevhen; Borysova, Olha; Kohut, Iryna; Імас, Євген; Борисова, Ольга; Когут, Ірина (Східноєвропейський національний університет ім.Лесі Українки, 2017)
The current relevance of the research. Over a significant period of human development disabled people were considered to be dependent and were regarded as weak, incapable, etc. Frequently, dependence, a result of disability, was exaggerated by teachers, family members and society. Adaptive physical culture and sportscan reduce dependence and social isolation, helping disabled people to become full members of society. Methods of the reseacrh: analysis and generalization of special, scientific and methodical literature, the Internet; standardized documents; comparative method, abstracting, logical and theoretical analysis. The results of the study. The main goal of lessons of adaptive physical culture and sports is to increase the level of social integration, welfare, reduction of the isolation of disabled people by changing public opinion about disability and their psychological attitude to themselves. To achieve this goal, first of all, it is necessary to reduce the level of discrimination which is associated with disability. Secondly, to encourage and stimulate disabled people to realize their own potential and, thirdly, to implement changes in society that promote the full social implementation of this category of people.At the same time, the competitions in adaptive sports, first was regarded as local, have turned into the widespread international sports events for athletes with different forms of disability. The success of the modern Deaflympics, Paralympic Games and World Games of Special Olympics is both a testimony and a factor in changing the attitude of society towards disability. Disabled people are not a burden or an issue of social expenditure, but they are assets of a society that can make a significant contribution to its development and prosperity. It is necessary to create appropriate conditions, eliminating physical and social barriers. Training sessions and competitions contribute to it in terms of creating a barrier-free environment, and changing public attitudes. Conclusions. Motor activity training of disabled people, their participation in competitions, can not only improve their physical, mental, leadership and other qualities, promote the development of communicative abilities, self-confidence, confidence in their own abilities, but also provide the preconditions for maximum full-fledged social integration of disabled people, as well as the humanization of public relations in general. Актуальність. Протягом значного періоду розвитку людства особи з інвалідністю вважалися залежними і розглядалися як слабкі, недієздатні, невмілі і т. п. Найчастіше, залежність, що виникає внаслідок інвалідності, є перебільшеною педагогами, членами сім’ї і суспільством. Адаптивна фізична культура і спорт здатні зменшити залежність і соціальну ізольованість, допомагаючи особам з інвалідністю стати повноправними членами суспільства. Методи дослідження: аналіз і узагальнення спеціальної та науково-методичної літератури, інформаційних ресурсів мережі Інтернет; програмно-нормативних документів; компаративний метод, абстрагування, логіко-теоретичний аналіз. Результати дослідження. Основною метою занять адаптивною фізичною культурою і спортом є підвищення рівня соціальної інтеграції, добробуту, зменшення ізоляції осіб з інвалідністю шляхом зміни громадської думки про інвалідність і психологічного ставлення їх до самих себе. Для досягнення поставленої мети, в першу чергу, необхідно знизити рівень дискримінації, пов’язаної з інвалідністю. По-друге – заохочувати і стимулювати осіб з інвалідністю, щоб вони усвідомили їх власний потенціал і, по-третє, здійснити зміни в суспільстві, що сприяють повноцінної соціальної реалізації зазначеної категорії осіб. У той же час, змагання в адаптивному спорті, що починалися як локальні, перетворилися в масштабні міжнародні спортивні заходи для спортсменів з різними формами інвалідності. Успіх сучасних Дефлімпійських, Паралімпійських ігор та Всесвітніх ігор Спеціальних Олімпіад є одночасно і свідоцтвом, і фактором зміни ставлення суспільства до інвалідності. Люди з інвалідністю – не тягар і не стаття соціальних витрат, а актив суспільства, який здатний внести вагомий внесок у його розвиток і процвітання. Необхідно лише створити відповідні умови, усуваючи фізичні та соціальні бар'єри. Тренувальні заняття та змагання сприяють цьому як в плані створення безбар'єрного середовища, так і зміни суспільних установок. Висновки. Заняття людей з інвалідністю руховою активністю,залучення їх до участі в змаганнях здатні не тільки вдосконалювати їх фізичні, психічні, розумові, лідерські та інші якості, сприяти розвитку комунікативних здібностей, самовпевненості, віри у власні можливості, а й забезпечити передумови для максимально повноцінної соціальної інтеграції осіб з інвалідністю, а також гуманізації суспільних відносин в цілому.
Роль рухової активності в соціальній ітеграціїї людей з інвалідністю.
Keywords: motor activity; adaptive physical culture and sport; disabled people; рухова активність; адаптивна фізична культура і спорт; особи з інвалідністю